2012
DOI: 10.1111/j.1559-1816.2012.00937.x
|View full text |Cite
|
Sign up to set email alerts
|

(S)he's Got the Look: Gender Stereotyping of Robots1

Abstract: Previous research on gender effects in robots has largely ignored the role of facial cues. We fill this gap in the literature by experimentally investigating the effects of facial gender cues on stereotypical trait and application ascriptions to robots. As predicted, the short‐haired male robot was perceived as more agentic than was the long‐haired female robot, whereas the female robot was perceived as more communal than was the male counterpart. Analogously, stereotypically male tasks were perceived more sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
193
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 402 publications
(226 citation statements)
references
References 39 publications
9
193
2
2
Order By: Relevance
“…Relatedly, the social-cues hypothesis (Louwerse, Graesser, Lu, & Mitchell, 2005) explained that adding human features as social cues on the robot like facial expression, voice, and physical presentation could enhance the chance for a human to perceive the technology more positively. This hypothesis was also supported by findings in several studies (Andrist, Spannan, & Mutlu, 2013;Cooney, Dignam, & Brady, 2015;Eyssel & Hegel, 2012).…”
Section: Introductionsupporting
confidence: 78%
“…Relatedly, the social-cues hypothesis (Louwerse, Graesser, Lu, & Mitchell, 2005) explained that adding human features as social cues on the robot like facial expression, voice, and physical presentation could enhance the chance for a human to perceive the technology more positively. This hypothesis was also supported by findings in several studies (Andrist, Spannan, & Mutlu, 2013;Cooney, Dignam, & Brady, 2015;Eyssel & Hegel, 2012).…”
Section: Introductionsupporting
confidence: 78%
“…Participants had to judge to what extent they would use the robot for a list of 12 gender stereotypical tasks that were adapted from [2]. Six tasks were defined as stereotypically male (e.g., "to transport goods", a = .84).…”
Section: Dependent Measuresmentioning
confidence: 99%
“…Therefore, the present research sought to investigate the effects of robot body shape on gender stereotypical judgments about allegedly male vs. female robots. Like [2], we explored the attribution of gender stereotypical traits such as communion and agency or warmth and competence, respectively [5][6][7]. Stereotypes can also impact peoples' trust in others [7].…”
mentioning
confidence: 99%
“…This research is based on prior findings showing that humans can observe a robot's expressed behaviors [29] [30] [31]. Previous research has shown that people use visual gender cues as a basis for their judgments about social robots [32] and react on social robotic [33] behavior.…”
Section: Moritz Merklementioning
confidence: 99%